A class by Herself : protective laws for women workers, 1890s-1990s - Woloch, Nancy, 1940- (Politics and society in twentieth-century America., 2015)
"A Class by Herself explores the historical role and influence of protective legislation for American women workers, both as a step toward modern labor standards and as a barrier to equal rights. Spanning the twentieth century, the book tracks the rise and fall of women-only state protective laws--such as maximum hour laws, minimum wage laws, and night work laws--from their roots in progressive reform through the passage of New Deal labor law to the feminist attack on single-sex protective laws in the 1960s and 1970s. Nancy Woloch considers the network of institutions that promoted women-only protective laws, such as the National Consumers' League and the federal Women's Bureau; the global context in which the laws arose; the challenges that proponents faced; the rationales they espoused; the opposition that evolved; the impact of protective laws in ever-changing circumstances; and their dismantling in the wake of Title VII of the Civil Rights Act of 1964. Above all, Woloch examines the constitutional conversation that the laws provoked--the debates that arose in the courts and in the women's movement. Protective laws set precedents that led to the Fair Labor Standards Act of 1938 and to current labor law; they also sustained a tradition of gendered law that abridged citizenship and impeded equality for much of the century. Drawing on decades of scholarship, institutional and legal records, and personal accounts, A Class by Herself sets forth a new narrative about the tensions inherent in women-only protective labor laws and their consequences."--